Plastid introgression and evolution of African miombo woodlands: New insights from the plastome‐based phylogeny of Brachystegia trees. (7th January 2021) - Boom, Arthur F.; Migliore, Jérémy; Kaymak, Esra; Meerts, Pierre; Hardy, Olivier J.
Abstract: Aim: Miombo woodlands form a characteristic vegetation type covering 2.7 million km 2 in southern and eastern Africa. Despite their wide geographical extent, their origin, floristic and spatial evolution through time remain understudied. To fill this gap, we studied the evolution of Brachystegia trees, one of the most representative genera of these woodlands (20 species), also represented in Guineo‐Congolian rain forests (8 species). Location: Tropical Africa, Guineo‐Congolian forests and Zambezian savannas. Taxon: Brachystegia genus. Methods: We used a genome skimming approach to sequence the plastomes of 45 Brachystegia samples, covering 25 of the 29 existing species, and one outgroup ( Julbernardia paniculata ). The phylogeny of the plastomes was reconstructed and time‐calibrated. We tested if the genetic divergence between lineages reflected taxonomic and/or geographical distances using Mantel tests. Finally, we inferred the evolutionary history of Brachystegia based on the age and spatial distribution of its lineages. Results: Surprisingly, species represented by multiple specimens appear rarely monophyletic while plastid clades display strong geographical structuring, independently of the species. Two main clades separate woodland and rain forest species, which diverged during the late Miocene–Pliocene (95% HPD = 2.78–8.59 Ma). In miombo woodlands, three subclades occur in parapatry along an East–West axis, ranging from Angola to East Africa. Their divergence started from the Plio‐Pleistocene (95% HPD = 1.17–3.69 Ma). Divergence dates (TMRCA) within miombo subclades decrease from East Africa (1.53 Ma) to Angola (0.76 Ma). Main conclusions: Brachystegia plastomes appear unreliable to identify species, probably due to species introgression leading to recurrent chloroplast captures. However, they prove very informative for tracking the past dynamics of the genus, and suggest a historical westwards expansion of miombo Brachystegia, and possibly of miombo vegetation, during the Plio‐Pleistocene. Further investigations using nuclear DNA are needed to assess the species tree as well as speciation and hybridization events between species.